A Copper Hydrometallurgical Plant Dysfunctions Related to Changes in the Feed Mineralogy: Case of ROM Ores from the Mutanda Deposit (DR Congo) - L. M. Shengo; M. F. Ilunga (New Approaches in Engineering Research Vol. 9, 2021)
In the former Katanga region of the Democratic Republic of Congo (DRC), the hydrometallurgical processing of copper–cobalt oxide ores enables producing copper as cathodes and cobalt as hydroxides. In the run-of-mine (ROM) ores used as the feed to hydrometallurgical plants, copper and cobalt are present mainly as malachite and heterogenite, respectively. These bearing minerals of copper and cobalt undergo sulphuric acid leaching under reducing conditions (Na2S2O5 or SO2) to produce leach liquors that are subjected to solvent extraction (SX) prior to electrowinning (EW) of copper. Cobalt is recovered from the copper’s SX raffinate through precipitation with magnesia. Cobalt is also precipitated from the low-grade pregnant leach solution (PLS) recovered during the counter-current thickening (CCT) washing of the sulphuric acid leaching solid residues. This research work aims at minimizing the slowdown in the settling velocity of solid matters experienced at the Mutanda Mining (Mumi) hydrometallurgical plant during the leach liquor recovery and clarification by thickening of suspended matters. Indeed, when the talcaeous mineral content increases in the ore used as feed, leach liquor clarification slows down, perturbing downstream operations consisting in the copper SX and EW, a phenomenon that results ultimately in the hydrometallurgical process dysfunctions. Based on the results given by leaching and settling tests conducted at laboratory scale to mimic the full size plant functioning, it has been concluded that the leach liquor recovery and successful clarification were achieved when the pulp was prepared with the specific gravity corresponding to 6% solids, which means processing the ore of which the talcaeous mineral content is maintained at either 20% or 60%. Additionally, the settling velocity of solids was significantly increased during the thickening tests when 80 g/t Superfloc N100 flocculent was added to the pulp given by the ore leaching.